Legal principles of the 1982 PIL Act, and filling the legal gaps in the Conflict of Laws matter in Serbian private international law: A different perspective - Marjanović Sanja (Anali Pravnog Fakulteta u Beogradu)
Despite the aspiration to comprehensively regulate legal relations, legislators can hardly avoid the occurrence of legal gaps, which may also arise due to the longevity of a statutory act that can no longer properly keep up with the development of a specific area of law. In Serbian Private International Law, the methods of filling legal gaps are regulated in Article 2 of the 1982 PIL Act, which provides three sets of principles: principles of the Act itself, the principles of the Serbian legal order, and the principles of PIL. However, certain international sources of Serbian PIL have engendered an unusual effect of hierarchical relationship with statutory conflict-of-laws rules, thus generating a different perception of gap-fillers (i.e. nationality principle, weaker party protection). In the paper, the author examines these issues, considering (to some extent) how legal gaps emerge in this branch of law, as well as the limits of characterization.